Treatment of skeletal Class III maxillo-mandibular relationship with the twin block appliance - Yosvany Herrero Solano; Luis Soto Cantero; Marcos Ros Sanatana; Yordany Arias Molina; Enma Xiomara Almeida Boza (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: Skeletal Class III maxillo-mandibular relationship is characterized by the non-physiological relationship between the dental arches, concave profile, maxillo-mandibular sagittal discrepancy and functional alterations that disturb the functioning of the stomatognathic system. In the national and international literature, there is no evidence of the effectiveness of treatment of Skeletal Class III maxillo-mandibular relationship with the use of twin block appliance. Objective: To evaluate the treatment of skeletal Class III maxillo-mandibular relationship with the use of twin block appliance. Material and Methods: A quasi-experimental intervention study was conducted in 43 patients with skeletal Class III maxillo-mandibular relationship at Manuel Cedeño Dental Specialties University Clinic during the period between January 2018 and June 2019. The study variables were: occlusion ratio, maxillo-mandibular skeletal classification, temporomandibular joint dysfunction and facial esthetics. The twin block appliance was applied to all patients as part of the orthopedic functional treatment. Results: Initially, 86,04 % of the patients had a mesioclusion, which was modified to neutroclusion in 81,39 %. Skeletal classification was corrected in 88,37 % of cases. Temporomandibular joint dysfunction improved to mild in 51,16 % of patients. Facial esthetics was not affected in 83,72 %. Conclusions: The ratio of dental occlusion and class III maxillo-mandibular skeletal relationship are corrected with the use of a twin block appliance, besides being a therapeutic choice that improves dysfunction of the temporomandibular joint and facial esthetics in patients with this dentomaxillofacial anomaly.